2020
DOI: 10.1007/s00109-020-01978-9
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling in kidney: the initiator or terminator?

Abstract: The kidney is a key organ in the human body that excretes toxins and sustains the water–electrolyte balance. During embryonic development and disease progression, the kidney undergoes enormous changes in macrostructure, accompanied by a variety of microstructural histological changes, such as glomerular formation and sclerosis, tubule elongation and atrophy, interstitial establishment, and fibrosis progression. All of these rely on the frequent occurrence of cell death and growth. Notably, to overcome disease,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 132 publications
0
21
0
Order By: Relevance
“…Accordingly, Wnt signalling is a key activator of EMT in conditions of injury [ 85 ]. Moreover, with evidence that Wnt/β-catenin signalling promotes the expression of numerous genes, including fibronectin, FSP1, Snail1, MMP7 and cyclin D1, it is not surprising that attenuation of this signalling cascade is associated with improved renal function, reduced EMT [ 86 ] and diminished inflammation [ 87 ] and fibrosis [ 80 , 88 ]. Consequently, it could, in part, account for the TGFβ1-induced increased expression and secretion of extracellular matrix proteins ( Figure 5 ), proinflammatory cytokines and chemokines observed in this study ( Figure 6 and Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Wnt signalling is a key activator of EMT in conditions of injury [ 85 ]. Moreover, with evidence that Wnt/β-catenin signalling promotes the expression of numerous genes, including fibronectin, FSP1, Snail1, MMP7 and cyclin D1, it is not surprising that attenuation of this signalling cascade is associated with improved renal function, reduced EMT [ 86 ] and diminished inflammation [ 87 ] and fibrosis [ 80 , 88 ]. Consequently, it could, in part, account for the TGFβ1-induced increased expression and secretion of extracellular matrix proteins ( Figure 5 ), proinflammatory cytokines and chemokines observed in this study ( Figure 6 and Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β‐catenin signalling is a conserved development pathway, 33 and however, it is reactive in multiple kinds of kidney diseases 34 . Interestingly, we have found that it is also overactivated in aged kidneys 6 .…”
Section: Discussionmentioning
confidence: 66%
“…Wnt/β-catenin signalling is a conserved development pathway, 33 and however, it is reactive in multiple kinds of kidney diseases. 34 Interestingly, we have found that it is also overactivated in aged kidneys. 6 The activation of β-catenin is accompanied by the loss of mito- could be activated by Wnt-triggered inhibition on its degradation 35 and also could be stimulated by GPCR-induced signal wave.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In the canonical pathway, Smad2 and Smad3 are two key downstream mediators of TGF-β receptor that are highly activated in renal fibrosis ( 35 ). Subsequently, activated Smad2 and Smad3 first complexed with Smad4 ( 36 ), then translocated into the nucleus to transcriptionally regulate pro-fibrotic molecules expression, including collagens, fibronectin, and alpha-smooth muscle actin ( 37 39 ), thereby facilitating fibrotic responses. However, each Smads protein is functionally distinct in the pathogenesis of CKD.…”
Section: Importance Of Tgf-β1 In Ckd Pathologymentioning
confidence: 99%